COMPARISON OF EASTERN AND WESTERN CULTURAL VALUE SYSTEMS FROM SOCIAL ASPECTS OF SOCIETY - Elyaroza, Elyaroza; Nabila, Maylani; Syahira, Istiana; Ulfa, Nurul Syafia (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2026)
This article aims to discuss the comparison between Eastern and Western cultural value systems in the social aspect of society. This is based on the fundamental differences between the two cultures, especially in terms of value orientation, patterns of social interaction and outlook on life. Then it also aims to examine its implications in the life of modern society. The method used is a qualitative approach with literature studies, through the collection of data from books, journals and relevant academic sources. The results of the study show that there are two cultures in the world, namely Eastern culture and Western culture. The two cultures are very different from each other. Eastern cultures tend to be oriented towards collectivism, social harmony and respect for norms and traditions. Meanwhile, Western culture emphasizes individualism, freedom, rationality, and individual independence. This difference is also seen in the aspects of ethics, education, and social relationship patterns. However, in the era of globalization, there is an exchange of values that causes the boundaries between the two cultures to become more dynamic. Therefore, understanding these two value systems is important in dealing with social changes in society Keywords: Comparison, Value System, Eastern Culture, Western Culture, Social Society.